2021
DOI: 10.1088/1755-1315/738/1/012035
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of lighting design in classroom for visual comfort (Case Study : Universitas Tridinanti Palembang Tower)

Abstract: Currently, the learning process in the classroom uses an LCD projector to display material on the white board. This LCD projector produces its own light, so the light source in the room will be added (beside daylight and artificial light). This condition makes a visual discomfort and not efficient energy uses. Based on previous study, the classroom users in UTP tower got visual comfort when the lamps were on 100% if projector used. But, in other condition when the projector is off, users will comfort if daylig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
0
0
0
Order By: Relevance
“…The implementation of daylighting strategies should be done in combination with a well-designed artificial lighting system. The daylight control mechanisms [41], individual lighting control features [33], and the development of activity-based lighting scenarios [40] enables to adjust lighting levels during periods with low availability of natural light or use the art studio during the evenings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The implementation of daylighting strategies should be done in combination with a well-designed artificial lighting system. The daylight control mechanisms [41], individual lighting control features [33], and the development of activity-based lighting scenarios [40] enables to adjust lighting levels during periods with low availability of natural light or use the art studio during the evenings.…”
Section: Discussionmentioning
confidence: 99%
“…In Madrid, to achieve the appropriate level of illuminance in classrooms, the application of LED lighting systems and white paint of the walls was suggested [39]. Setiati and Budiarto [40] suggest developing several lighting scenarios based on the schedule and the use of the necessity of the whiteboard use and grouping the lighting sources in a way that provides the optimal visual comfort using natural and artificial light. Dong et al [41] propose using curtains for natural light control in combination with sensors, which can adjust artificial light at the desired intensity.…”
Section: Lighting Design Strategies In Schools At Lower Latitudes Of ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The reflected light (brightness) is always less than the incident light (illumination), therefore the RF is always less than 1, and since reflected light is always little, the RF is never 0. Artificial lighting systems play an important role in the energy consumption due to incorrect placement of lamp points and parallel lighting zoning will result in excessive use of artificial lighting (Setiati & Budiarto, 2021). Previous study conducted by Vollaro et al, (2014) has suggested that lighting design by means of energy consumption assessment connects with lighting requirements.…”
Section: Introductionmentioning
confidence: 99%